Emigration and the Limits of Public Policy in Quebec and Nova Scotia, 1867–1900 - Lacroix, Patrick (Journal of the Royal Nova Scotia Historical Society)

(untitled) (Royal Nova Scotia Historical Society, 2022)
In the nineteenth century, many regions of Canada faced a crisis that sometimes seemed existential: uneven economic growth resulted in sustained emigration to the United States. Far from being unique to French Canadians in the St. Lawrence River valley, whose story is better known, the exodus touched Nova Scotia and intersected with debates over industrialization and federal-provincial relations. Everywhere the issue posed a challenge to elected officials. However, diagnosing the problem differently and wielding a variety of policy tools, these officials could not agree on means of generating opportunities comparable to those of the US Northeast. Whereas Quebec recommitted itself to an agrarian vision of domestic colonization, a vigorous critique of Confederation emerged in Nova Scotia. The debates in these two provinces should inspire scholars to study emigration as the foremost national challenge of the late nineteenth century and integrate historical voices who exemplify the many political paths available to Canadian electors.